Neurogenic thoracic outlet syndrome caused by infection and scar tissue formation in the clavicle trajectory in a patient without a clavicle - Stijn B.J. Teijink; Niels Pesser; Bart F.L. van Nuenen; Joep A.W. Teijink (Annals of Vascular Surgery - Brief Reports and Innovations, 2023)
Introduction: We present a patient that suffers from severe neurogenic thoracic outlet syndrome (NTOS) complaints without having a clavicle bone. This exceptional case shows the importance of scar tissue generation as an important cause for neurogenic thoracic outlet syndrome, especially in patients with previous surgery or infection in the thoracic outlet region. Report: The presented patient was a 60-year-old women with typical NTOS complaints. Her complaints started when she was 40 years of age and were progressive over the last two years. Her medical history revealed a complicated right clavicle fracture. At the age of five, the fracture caused a serious infection that was treated with ointments, weekly injections, and antibiotics. At the age of seven, the clavicle was removed. In a multidisciplinary meeting it was concluded that she suffered NTOS, most likely due to prolonged infection in her childhood and extensive scar tissue in the trajectory of the lost clavicle. During surgery a substantial amount of dense fibrotic tissue surrounding the brachial plexus was found and removed, which confirmed the hypothesis of scar tissue related compression with subsequent complaints. The anterior and medial scalene muscles were also removed. The first rib was left in situ. The patient showed significant post-operative improvements measured with the DASH, CBSQ and TOS disability scale. She defines the outcome of surgery by the Derkash classification as ‘Good’. Discussion: This case report shows that compression of the brachial plexus compression can exist because of extensive scar tissue formation due to severe infection, without involvement of a clavicle and no relevant impact of the first rib. The formation of scar tissue in this patient led to disabled nerve gliding and extrinsic compression of the brachial plexus. Therefore, history of infection in the thoracic outlet should be considered as predisposing factor for the development of NTOS complaints.